KARAKTERISTIK KEMIRINGAN LERENG, KEDALAMAN DAN KECERAHAN DALAM MENDUKUNG AKTIVITAS PERMANDIAN DI PANTAI MARUMASA KECAMATAN BONTOBAHASI KABUPATEN BULUKUMBA - Hasriyanti, Hasriyanti; Ansarullah, Ansarullah (Jurnal Environmental Science, 2019)
This study aims to explain the characteristics of the slope, depth, and brightness, as supporting activities on the Marumasa beach, Bontobahari sub-district, Bulukumba district. This type of research is a survey research, with variable slope, depth and brightness of Marumasa coastal waters. Primary data in the form of direct measurement data in the field, and secondary data in the form of the Earth Map of Bulukumba Regency, Tanah Beru sheet, Sheet 2110-14 The results showed that Marumasa Beach has various slopes, the lowest slope with type I class or flat is between (0-2%) covering 1.17 hectares with a percentage of 45.88%, slope with type II class or sloping that is between (3 -8%) area of 0.73 hectares with a percentage of 28.63%, slope with type III class or sloping that is between (9-25%) area of 0.52 hectares with percentage of 20.39% and highest slope with type class IV or steep (26-40%) area of 0.13 hectares with a percentage of 5.10%. The results of the measurement of the depth value that has been corrected with the MSL value that is at the deepest A2 point, from the measurement results in the field has obtained the depth of the A2 point about 0.12 m and the lowest point is at point C1 with a measurement depth of 0.29 m with a correction value 0.10 m. The results of the measurement of the waters brightness at Marumasa Beach showed that the brightness value was 100% from all observation points. Marumasa beach characteristics are in the category S = very suitable (highly suitable) to be used as beach tourism (beach bathing).